The ethical and economic aspects of sexual medicine: recommendations from the Fifth International Consultation on Sexual Medicine (ICSM 2024) - Sidney Glina; Joachim Osur (Sexual Medicine Reviews, 2025)
Introduction: In recent years, the field of sexual medicine has undergone major transformations brought about by the internet and concern with genital performance and aesthetics. On the other hand, economic transformations have increased barriers to better care and sexual education. Methods: Given the emerging knowledge of this topic, we conducted a narrative review of the extant literature through wide searches in PubMed and Google and on global websites relevant to this topic, such as the World Health Organization, the United Nations, and others. The content of this paper was reviewed by all the authors, discussed where disagreements occurred, or additional perspectives were needed, and further literature was incorporated. Results: The Internet has made valuable contributions to the dissemination of sexual health education, but it has also promoted non-evidence based information that can contribute to sexual dysfunctions and has contributed to sexual exploitation and cyberbullying. Of concern is the rise of an Internet-based industry that promotes and dispenses dietary supplements. Liberal, unfettered marketing has brought the dissemination of products that, at best, do not deliver the desired result, and at worst, are adulterated and become a threat to individual and public health. In the context of false advertising, men’s anxiety about penis size has been exploited. Advertising of techniques that would produce penis enlargement preys on these anxieties without evidence to support efficacy of these techniques. Economic barriers have impeded men’s ability to access sexual healthcare. The lack of coverage by health plans, the lack of trained professionals, and the costs of exams and treatments impede access to sexual healthcare in many parts of the world. Conclusions: We recommend that doctors inform patients of the risks of non-evidence-based practices and that the International Society of Sexual Medicine produce evidence-based information accessible to the general public and seek to work toward finding solutions to existing economic barriers.
This is an Open Access article distributed under the terms of the Creative Commons Attribution License (https://creativecommons.org/licenses/by/4.0/), which permits unrestricted reuse, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: internet; dietary supplements; penile enlargement; health economic; ethic; sexual health.